Implementation of Addie Model in Hisbah Reflection through Mobile Phone Application - Makhsin, Mardzelah; Hj Azid Aziz, Nurulwahida; Nurmaya Jumiran, Siti; Fadhli Ilias, Mohamad; Amirul Fahmi Mat Sukeri, Mohamad (International Journal of Engineering and Technology, 2018)
Hisbah Reflection a control practice behaviour based on al-â€˜amr bi al-maâ€™ruf wa al-nahy an al-munkar plays a big role in achieving the goals of National Education Philosophy. Hisbah Reflection seen as an alternative or best control mechanism in driving the youth to behave noble. This study focuses on the development of Hisbah Reflection mobile applications as mobile phone is the closest device to us. The aims of this study is develop a mobile phone application based on the Hisbah Reflection components, namely Musyaratah (promise of heart), Muraqabah (behavior observation), Muhasabah (mind accountability), Muaqabah (spiritual reinforcement), Mujahadah (desire resistance) and Muatabah (soul purification). This study involving 50 students as respondents and the implementation of ADDIE model (Analysis, Design, Development, Implementation and Evaluation) throughout the development process. The data collection process involves questionnaire as a research instrument and data were analyzed in descriptive (frequency, percentage, and mean) using the Statistical Package for Social Sciences (SPSS). The findings of Hisbah Reflection Practice Level and Mobile Applications Results shows that respondents are satisfied with the application. The proposed improvements were also made to overcome any weaknesses detected.Â Â